ODE No. 818

\[ y'(x)=\frac {y(x)}{x \left (x y(x)^4+x y(x)^3+x y(x)-1\right )} \] Mathematica : cpu = 0.233857 (sec), leaf count = 34

DSolve[Derivative[1][y][x] == y[x]/(x*(-1 + x*y[x] + x*y[x]^3 + x*y[x]^4)),y[x],x]
 

\[\text {Solve}\left [\frac {y(x)^3}{3}+\frac {y(x)^2}{2}+\frac {1}{x y(x)}+\log (y(x))=c_1,y(x)\right ]\] Maple : cpu = 0.217 (sec), leaf count = 34

dsolve(diff(y(x),x) = y(x)/x/(-1+x*y(x)+x*y(x)^3+x*y(x)^4),y(x))
 

\[y \left (x \right ) = {\mathrm e}^{\RootOf \left (-2 x \,{\mathrm e}^{4 \textit {\_Z}}-3 x \,{\mathrm e}^{3 \textit {\_Z}}+6 c_{1} x \,{\mathrm e}^{\textit {\_Z}}-6 \textit {\_Z} x \,{\mathrm e}^{\textit {\_Z}}-6\right )}\]